(untitled) (Bangladesh Journal of Botany, 2019)
Pre-application of plant extracts as resistance inducers provided protection of tomato plants and reduced wilt incidence from 84.46 - 8.40% with the minimum in garlic extract treated seedlings followed by neem and zinger extract representing 10.70 and 11.90%, respectively. Treatment with plant extracts as inducers prior to challenge inoculation sensitized the seedlings to produce increased levels of soluble protein with the maximum in garlic extract treated seedlings representing 29.5, 32.40, and 31.6 mg/g of fresh leaves of 5, 10 and 15 days of pathogen inoculation whereas, in case of control-1 and control-2 the values were 21.80, 22.50 and 22.00 mg/g and 18.98, 20.90 and 19.90 mg/g of fresh leaves, respectively. A high content of phenol, which is an indicator of first stage of defence mechanism, was also recorded maximum in garlic extract treatment as 2.09, 2.26 and 2.18 mg/g of fresh leaves against 1.50, 1.59 and 1.58 mg/g and 1.40, 1.50 and 1.46 mg/g in case of control-1 and control-2 at 5, 10 and 15 days of pathogen inoculation. Correlation coefficient between disease incidence with soluble protein (r = –0.572) and total phenol (r = –0.533) showed a negative correlation with disease incidence.